BASICS OF THEORETICAL APPROACHES OF TECHNOLOGICAL PROCESSES WITH REGULAR TOSSING OF THE GRANULAR MEDIUM - Eliseev, A V; Artyunin, A I; Kargapolcev, S K; Dimov, A V (Proceedings of the Mongolian Academy of Sciences, 2017)
Vibration interaction is used for development of modern technological processes in which required quality of product is provided due to interaction of the granular medium with the vibrating surface. The paper is devoted to development of mathematical models and estimation criteria form of movement, taking into account the effect of unilateral constraints, in dynamic interactions of elements of vibration technological processes as applied to increase the reliability and quality of vibrational machines. The study is focused on the formation of theoretical ideas about the dynamic interactions of a solid body with the vibrating surface based on the development of mathematical models by introducing of additional external forces and elastic ties with unilateral contact, including mathematical models of gapless movement of the compounded solids. In terms of practical applications the task is to develop and to approve experimentally the opportunities of the measuring devices fixing the modes of continuous tossing. According to the research the generalized approach to problems of dynamic synthesis of vibration technology implemented in continuous tossing the introduction of additional forces is developed. The basis of the approach is the introduction of the concept of the function of the gap, allowing to justify the construction of forms of motion of material particles in accordance with certain criteria, reflecting the properties of the trajectories of motion of material particles in the interaction with the vibrating surface. The mathematical models to determine the conditions for the formation of dynamic reactions in the vibrational structure consisting of several interconnected elements, including the possibilities of their pre-pressing by elastic ties and power factors is offered. The measuring device fixing the modes of continuous tossing is developed and experimentally approved.